Reliability of pheromone trap catches and maize plant damage as criteria for timing fall armyworm control interventions in humid forest agroecology of central Africa - Abang, A.F.; Nanga, S.N.; Ndanda, R.M.O.; Doumtsop Fotio, A.R.P.; Gonder, M.K.; Kouebou, C.; Suh, C.; Fotso Kuate, A.; Fiaboe, K.; Hanna, R. (Oxford University Press, 2022)
Control of fall armyworm (FAW) Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) since its invasion of Africa still depends on pesticides. Early detection of adults is considered the key to the success of larvae control in the crop field. However, FAW control thresholds based on current monitoring techniques are not well established in Africa. We investigated the efficacy of moth capture frequencies and FAW incidence levels as decision tools for FAW management. Experiments were conducted over two maize cropping seasons during which FAW incidence, severity, and larvae count were recorded during destructive sampling after the application of a homologated insecticide. During the first season, the FAW incidence ranged from 37.5 ± 5.6% in the 25% incidence threshold treatment to 48.1 ± 8.1% in the control. During the second season, the incidence was significantly lower in the 25% incidence threshold treatment (55.8 ± 5.7%) compared with the control (75.7 ± 3.0%). Over the two seasons, no significant difference in FAW damage severity was recorded between the treatments and control. The highest number of larvae per plant (4.0 ± 0.6) was observed in the 10% incidence threshold treatment. Insecticide application did not consistently contribute to reducing FAW incidence and observed plant damage did not translate into yield loss. FAW control needs further investigation to establish a threshold above which damage translates into yield loss, thus necessitating control intervention.